Penilaian Risiko Untuk Meningkatkan Resiliensi Jalan Tol (Studi Kasus: Jalan Tol Semarang-Batang Dan Jalan Tol Bali-Mandara) - Aulia, Askia esa; Ariyani, Ariyani; Birahmatika, Lilla Anjani (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
This study aims to identify and evaluate the risks affecting toll road revenue reduction and to develop mitigation strategies to enhance the resilience of the toll road sector. Case studies were conducted on the Semarang–Batang and Bali–Mandara toll roads. Using a combination of literature review, expert validation, and stakeholder surveys, 22 risk variables were identified and analyzed through a probability-impact matrix and descriptive methods. Results show that the most critical risk on the Semarang–Batang toll road is the delay in toll rate adjustments due to failure to meet Minimum Service Standards (SPM), which scored the highest severity value (15.000) and is classified as an extreme risk. In contrast, the Bali–Mandara toll road’s top risk is inflation rate fluctuations, with a severity score of 16.174. These differences are attributed to regional characteristics, surrounding infrastructure, and local economic conditions. Proposed mitigation strategies include government-backed revenue guarantees, concession extensions, flexible tariff policies, and improved operational and maintenance practices. Risk handling also incorporates traffic projection reviews and feasibility-based scenario planning. The findings of this study provide valuable insights for toll road operators (BUJT) and policymakers to develop risk management strategies that support the sustainability of toll road operations, particularly under uncertain conditions such as pandemics or global economic pressures.